Initial public offering (IPO) (Henry Stewart Talks, 2025)
IPO definition and purpose, IPO process and stakeholders, Stock exchanges and listing choices, Liquidity and market capitalization, Regulatory challenges in IPOs, IPO pricing and underpricing, Trends and IPO alternatives